1994
DOI: 10.1038/hdy.1994.93
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype analysis and optimization of mitotic index in Picea mariana (black spruce) preparations from seedling root tips and embryogenic cultures

Abstract: The effect of hydroxyurea and coichicine solutions on mitotic index was investigated in embryogenic suspensions and in seedling root tips of Picea mariana. Hydroxyurea treatment and 0.6 per cent coichicine solution significantly increased the quantity of mitotic cells which were mostly in the metaphase stage. The highest mitotic index was observed in cells of embryogenic suspensions. The embryogenic lines were cytologically stable and their utilization for karyotype studies and technique development holds grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This model contemplates that structural characteristics of the genome restrict the posi- tion and the number of breaks that could occur and the type of rearrangements that could form. Even though both mechanisms would have similar results, most available molecular and chromosome data favor the position that chromosomal mutations are not only nonrandom but are constrained by chromosome structure (i.e., to the type of change that can be produced) (Peters 1982;Shaw et al 1983;Narayan 1998;King 1993;Seijo and Fernandez 2003). The pattern of evolution at the molecular and subchromosomal levels suggests that, in general, species within this group and other pines evolved in a concerted fashion, maintaining the general karyotype morphology.…”
Section: Chromosome Evolution and Identificationmentioning
confidence: 88%
See 3 more Smart Citations
“…This model contemplates that structural characteristics of the genome restrict the posi- tion and the number of breaks that could occur and the type of rearrangements that could form. Even though both mechanisms would have similar results, most available molecular and chromosome data favor the position that chromosomal mutations are not only nonrandom but are constrained by chromosome structure (i.e., to the type of change that can be produced) (Peters 1982;Shaw et al 1983;Narayan 1998;King 1993;Seijo and Fernandez 2003). The pattern of evolution at the molecular and subchromosomal levels suggests that, in general, species within this group and other pines evolved in a concerted fashion, maintaining the general karyotype morphology.…”
Section: Chromosome Evolution and Identificationmentioning
confidence: 88%
“…In recent years, modified chromosome spread techniques have been developed that provide a large number of high quality metaphase cells Klimaszewska 1994, 1995;Nkongolo 1996Nkongolo , 1999IslamFaridi et al 2007;Mehes-Smith et al 2011). Consistency in the detection of the locations of secondary constrictions has been improved (see Fig.…”
Section: Comparative Karyotype Analysis In the Pinaceaementioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, Isabel et al (1993) found no variation in RAPD profiles in somatic embryos from three black spruce lines. Nkongolo and Klimaszewska (1994) and Nkongolo (1995) detected no aneuploidy nor any other abnormalities in black, red and white spruce lines after extended culture. Similar findings were made for 4 lines from 2 larch species after 5 years of culture (Nkongolo and Klimaszewska 1995).…”
mentioning
confidence: 88%